2016
DOI: 10.2147/copd.s99156
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of synchronized intermittent mandatory ventilation and pressure-regulated volume control ventilation in elderly patients with acute exacerbations of COPD and respiratory failure

Abstract: BackgroundCOPD is the third leading cause of death worldwide. Acute exacerbations of COPD may cause respiratory failure, requiring intensive care unit admission and mechanical ventilation. Intensive care unit patients with acute exacerbations of COPD requiring mechanical ventilation have higher mortality rates than other hospitalized patients. Although mechanical ventilation is the most effective intervention for these conditions, invasive ventilation techniques have yielded variable effects.ObjectiveWe evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A study including 39 older intubated patients with chronic obstructive pulmonary disease compared PRVC and SIMV-VC modes and evaluated the efficacy of PRVC mode and its prevention of pulmonary barotrauma. Assessment of respiratory mechanics, arterial blood gas analysis, and vital signs at 2-4 h and at 48 h showed that PRVC resulted in rapid improvement in arterial blood gas parameters while maintaining low peak inspiratory pressure [25].…”
Section: Discussionmentioning
confidence: 99%
“…A study including 39 older intubated patients with chronic obstructive pulmonary disease compared PRVC and SIMV-VC modes and evaluated the efficacy of PRVC mode and its prevention of pulmonary barotrauma. Assessment of respiratory mechanics, arterial blood gas analysis, and vital signs at 2-4 h and at 48 h showed that PRVC resulted in rapid improvement in arterial blood gas parameters while maintaining low peak inspiratory pressure [25].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding advanced MV modes, SIMV performance remains inferior in the literature, in studies comparing pressure-regulated volume control ventilation, which presents better respiratory conditions and hemodynamic stability [ 1 ]. Thus, advanced MV modes are more often favored than SIMV [ 1 , 26 ]. Other studies compared SIMV with adaptive support ventilation (ASV) as a weaning method, where ASV had shorter duration of MV compared with SIMV [ 27 , 28 ], improved medical outcomes, recovery of airway function, decreased respiratory muscle work and more stable chest pressure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRVC has demonstrated improved oxygenation, improving arterial blood gas results and lowering peak inspiratory pressures (PIPs) in patients with COPD, acute respiratory distress syndrome (ARDS), and post post-cardiac surgical patients. [15][16][17][18][19] However, the small sample size of the above studies with the absence of larger randomized controlled trials has not demonstrated any greater advantage of PRVC compared to other modes. The ventilator settings for PRVC include a target V T , RR, upper pressure limit, inspiratory time, PEEP, and FIO 2 .…”
Section: Advanced Modes Of Invasive Mechanical Ventilation Pressure-rmentioning
confidence: 99%